2023
DOI: 10.1002/adom.202202548
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal Hyperbolic Metasurfaces Enhance Spontaneous Emission of Nitrogen‐Vacancy Centers in Nanodiamond

Abstract: and spin-selective optical transitions of NV centers form the basis of optically detected magnetic resonance and have fostered a plethora of interest in developing quantum biosensing methods, as exemplified by the nanoscale magnetometry [1e,2a] and spinenhanced ultrasensitive diagnostics. [1a-c] Yet, the achievable sensitivity and temporal resolution are compromised by inefficient photon generation and extraction from excited NV centers owing to their long radiative lifetime, which ranges from 10 to 30 ns d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…proposed a fully complementary route to modify the spontaneous emission from the NV center featuring a pyramidal metasurface. [ 211 ] The NV centers in nanodiamonds were measured by fluorescence lifetime imaging microscopyon the fabricated pyramidal cell surface, and numerically obtained results have been validated that the pyramidal metasurface provides a broadband enhancement mechanism in both spectral and spatial domains. The introduction of the metasurface paves the way for the realization of chip‐based ultrafast photonic devices and the development of spin‐enhanced quantum optical sensing strategies.…”
Section: Applications and Technologiesmentioning
confidence: 87%
“…proposed a fully complementary route to modify the spontaneous emission from the NV center featuring a pyramidal metasurface. [ 211 ] The NV centers in nanodiamonds were measured by fluorescence lifetime imaging microscopyon the fabricated pyramidal cell surface, and numerically obtained results have been validated that the pyramidal metasurface provides a broadband enhancement mechanism in both spectral and spatial domains. The introduction of the metasurface paves the way for the realization of chip‐based ultrafast photonic devices and the development of spin‐enhanced quantum optical sensing strategies.…”
Section: Applications and Technologiesmentioning
confidence: 87%
“…(Gao et al, 2023;Lu et al, 2023;Rippa et al, 2024). The present technique of specific RNA quantification involves complementary base pairing between a The fluorescence intensity images of NV centres measured on the pyramidal metasurface, the Ag nanopyramid, and the quartz substrate, respectively, in a dimension of ≈14 μm × 14 µm with an excitation wavelength of 532 nm (Zheng et al, 2023).…”
Section: In Molecular Sensingmentioning
confidence: 99%
“…[ 31 ] Apart from these passive applications of metasurfaces, recently, metasurface with hyperbolic dispersion is proposed as a viable platform to control the quantum emitter emission properties. [ 32 ] Thus, by modulating the interplay between the excited multipoles in metasurfaces that results in strong localized fields, significant emission enhancement for quantum emitters can be achieved due to the increased interaction with the local density of states (LDOS). However, it has been observed that metasurfaces coupled with single quantum emitters can boost the emission rate and directionality of the emitted single photon, which opens new avenues of metaphotonics in quantum technologies.…”
Section: Introductionmentioning
confidence: 99%